Analisis Strategi Pemasaran Produk di Kawasan Bukit Lawang - Purba, Yohan Duma Sari; Samosir, Nurhayati (Politeknik Pariwisata Medan, 2024)
This research aims to analyze product marketing strategies in the Bukit Lawang area using Ansoff Matrix Analysis. The Bukit Lawang area is one of the famous tourism destinations in North Sumatra, Indonesia, especially known for its natural orangutan habitat and natural beauty. The research method used is a descriptive analysis method, with a focus on Ansoff Matrix Analysis which includes four strategies: market penetration, market development, product development, and diversification. Data was collected through field observations, interviews with relevant stakeholders, and documentation studies. The research results show that the market penetration strategy can be implemented by increasing tourism promotion in the Bukit Lawang area and increasing cooperation with travel agents. Market development strategies are recommended through increased promotion to international markets and diversification of market segments, such as accommodating expatriate and family tourists. Product development can be realized through the introduction of new tour packages, developing tourism infrastructure, and improving service quality. Finally, a diversification strategy can be implemented by developing different tourism products or expanding the business into other sectors related to tourism